What Can Disability Learn from the Breastfeeding Wars? - Angela Lea Nemecek (Disability Studies Quarterly, 2011)
This paper uses disability and feminist perspectives to argue that the construction of breastfeeding in the workplace illuminates fundamental aspects of the construction of disability. Breastfeeding workers parallel disabled workers in many ways: both require accommodations, both often rely on prosthetic devices, and both have difficult achieving the kind of worker “independence” that contemporary workplaces value. By examining these parallels, and considering the subordinate status of interdependent bodies, this paper explores the implications of the feminist movement’s hesitation to rally behind breastfeeding rights. It also offers a new way of looking at the social model of disability as one that is capable of constructing disability even in the absence of impairment.
Keywords: disability; feminism; workers; social model of disability; breastfeeding; autonomy; independence; interdependence